TINGKAT KEPUASAN PEGAWAI ATAS PELAKSANAAN PROMOSI JABATAN PADA KANTOR BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN TAPANULI TENGAH - Jeniusman Ahmad Hutagalung; Rahmayanti Rahmayanti (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
This Thesis Research aims to determine the extent of employee satisfaction with the implementation of promotion in the office of the Regional Development Planning Agency (Bappeda) of Central Tapanuli Regency. The formulation of the problem in this study is how the level of employee satisfaction with the implementation of promotion in the office of the Regional Development Planning Agency (Bappeda) of Central Tapanuli Regency. The research design used was a quantitative analysis, in which the total population in this study were all employees in the Regional Development Planning Agency (Bappeda) of Central Tapanuli Regency totaling 67 and a sample of 45 people. Based on the results of the study showed that the relationship between job promotion and employee satisfaction is a very low category, where the calculation of correlation obtained 0.199. While the coefficient of determination is 4% while the remaining 96% can be influenced by other factors not discussed in this study. Simple linear regression obtained by the equation model Y = 21.235 + 0.365 X shows the relationship between promotion and employee satisfaction toward positive. Tcount value is smaller than ttable or 1.334 â‰¤ 1.68107 then the hypothesis proposed is rejected. So it can be concluded that Ha was rejected and Ho was accepted, namely there was no employee satisfaction with the promotion of position at the Regional Development Planning Agency (Bappeda) of Central Tapanuli Regency.